Tobias Barreto e Jean-Marie Guyau: Controvérsias em torno da religião e do sentimento religioso - Nunes, Antonio Vidal (Sofia, 2012)
Tobias Barreto e Jean-Marie Guyau: Controvérsias em torno da religião e do sentimento religioso